Photobiological implications of melanin photoprotection after UVB‐induced tanning of human skin but not UVA‐induced tanning. (5th January 2015) - Coelho, Sergio G.; Yin, Lanlan; Smuda, Christoph; Mahns, Andre; Kolbe, Ludger; Hearing, Vincent J.
Summary Repetitive suberythemal UVA and/or UVB exposures were used to generate comparable UV‐induced tans in human skin over the course of 2 weeks. To evaluate the potential photoprotective values of those UVA‐ and/or UVB‐ induced tans and to avoid the confounding issue of residual UV‐induced DNA damage, we waited 1 week before challenging those areas with a 1.5 MED of UVA+UVB after which we measure DNA damage. The results show that the type of UV used to induce skin pigmentation affects the redistribution of melanin in the skin and/or de novo melanin synthesis. The UVA‐induced tans failed to even provide a minimal SPF of 1.5, which suggests that producing a tan with UVA‐rich sunlamps prior to a holiday or vacation is completely counterproductive.